Design and frameworks with experiment for a basic guide of theoretical isnad al-hadith authenticity examination - Ibrahim, Nuzulha Khilwani Ibrahim; Samsuri, Suhaila; Abu Seman, Muhamad Sadry; Ahmed Ali, Ahmed El-Mogtaba Bannga; Kartiwi, Mira; Hasan Basari, Abd Samad (The Universal Academy of Science and Technology (UniTech), 2017)
These days, there are an increasing number of studies in ICT which has been done on the hadith domain in different levels of knowledge of hadith. Several studies have been conducted in IT to validate the Hadiths where most of them are based on the matching of test Hadiths with the authentic Hadiths in the database. However, there are limited computerized-based studies to authenticate the Hadiths based on scholars’ principles. Therefore, in this study, firstly, we need to identify the principles of isnad al-hadith authentication theoretically, which the specific criteria will be proposed based on previous studies and knowledge of Hadith. Secondly, a new mechanism will be developed to achieve the authentication of the new criteria of the isnad al-hadith. This mechanism development includes the integration between Islamic knowledge and Information Technology (IT) which we proposed to develop an algorithm based on existing framework with a new element of facts probing from Islamic knowledge. The accuracy of the authentication process on the knowledge domain of Hadith will be evaluated by domain experts through interviews.